The Contribution of ChatGPT, Digital Literacy, and Economic Literacy to The Study Outcomes of Economic Education Students Mediated by Self-Efficacy - Istiqomah Ahsanu Amala; Wening Patmi Rahayu; Heny Kusdiyanti; Jafalizan Md. Jali (STKIP Singkawang, 2025)
Technological progress requires the presence of intelligent economic people, able to create income, make wise economic decisions, and improve the welfare of life. Economic education that is responsive to technological developments is able to provide more relevant learning experiences. The success of current economic education students who are digital natives can be influenced by various aspects, such as the contribution of ChatGPT, digital literacy, economic literacy, and self-efficacy. This research aims to determine the influence of the contribution of ChatGPT, digital literacy, and economic literacy to study results which are mediated by the self-efficacy of economic education students. The research method uses a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) via the SmartPLS application version 3.3.9. The research results show that economic literacy has a large and effective contribution in increasing student self-efficacy and study results compared to the use of ChatGPT and digital literacy. There is still room for improvement to optimize the implementation of ChatGPT and strengthen digital literacy in achieving good study results